2017
DOI: 10.17559/tv-20150116001543
|View full text |Cite
|
Sign up to set email alerts
|

Construction costs forecasting: comparison of the accuracy of linear regression and support vector machine models

Abstract: Original scientific paper Each contract for a construction project has the costs as an essential element, so the accuracy of forecasting the construction costs can have an impact on the project realization, and also, on the project participants' business. Data for structures (75) were used for modelling with two predictive models: linear regression model (LR) and support vector machine (SVM) model, using Bromilow's model for cost and time relation and predictive modelling software DTREG. The mean absolute perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition, they require less memory space, are easy to use, and are generally less expensive. On the other hand, ANN-based models generally have a better level of accuracy in both regression and classification problems [27]. In addition, ANNs are preferable when the data does not adhere to loworder polynomial forms [28].…”
Section: Literature Analysismentioning
confidence: 99%
“…In addition, they require less memory space, are easy to use, and are generally less expensive. On the other hand, ANN-based models generally have a better level of accuracy in both regression and classification problems [27]. In addition, ANNs are preferable when the data does not adhere to loworder polynomial forms [28].…”
Section: Literature Analysismentioning
confidence: 99%
“…In addition, they are effective due to a well-defined mathematical expression, as well as the ability to explain the significance of each variable and the relationship between independent variables (Sodikov, 2005(Sodikov, , 2009. When there is only one predictor variable it is called simple linear regression (Meharie et al, 2022), and when there are several predictors, it is referred to as multiple linear regression (Petruseva et al, 2017;Meharie et al, 2022). Regression model equations can be expressed as follows (Kim et al, 2004;Sodikov, 2009):…”
Section: Cost Estimation Of Highway Bid Itemsmentioning
confidence: 99%
“…When there is only one predictor variable it is called simple linear regression (Meharie et al. , 2022), and when there are several predictors, it is referred to as multiple linear regression (Petruseva et al ., 2017; Meharie et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Linear regression is a method for modeling the relationship between one or more independent variables and one dependent variable (Petruseva et al , 2017). When there is only one independent variable and the relationship is linear it is called simple linear regression.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developed model was able to ECAM 29,7 predict the cost road construction project with 95% prediction accuracy by using seventy project cases. Petruseva et al (2017) applied and compared two predictive models: MLR and SVM model using 75 datasets to forecast the cost of construction projects. Comparison of the model results showed that the SVM forecast was substantially more reliable than the MLR.…”
Section: Support Vector Machinesmentioning
confidence: 99%